2019
DOI: 10.1590/fst.16018
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of minimally processed vegetables commercialized in Brasilia, DF, Brazil

Abstract: Fruits and vegetables are essential components of a human healthy diet and there are considerable evidences of the nutritional benefits associated with the regular consumption of fresh fruits and vegetables (Goodburn & Wallace, 2013; Maffei et al., 2013). Consequently, nowadays, there is a growing interest in healthy diets, which increased consumption of vegetables and caused an expansion of the market for minimally processed vegetables. These products meet the needs of their consumers because of changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…The most recent studies on the occurrence of foodborne pathogens in RTE-MPV in Brazil are summarized in Table 1, indicating that prevalence of Salmonella and L. monocytogenes ranges from 0.4% to 12.5% and from 0.6% to 3.1%, respectively. Except for the data of Cruz et al, 40 the results do not differ from those found in other countries (Table 2), where the reported prevalence of these pathogens range from 0.8% to 5% and from 0.6 to 4.3%, respectively.…”
Section: Occurrence Of Pathogenic Microorganisms and Foodborne Outbrecontrasting
confidence: 55%
“…The most recent studies on the occurrence of foodborne pathogens in RTE-MPV in Brazil are summarized in Table 1, indicating that prevalence of Salmonella and L. monocytogenes ranges from 0.4% to 12.5% and from 0.6% to 3.1%, respectively. Except for the data of Cruz et al, 40 the results do not differ from those found in other countries (Table 2), where the reported prevalence of these pathogens range from 0.8% to 5% and from 0.6 to 4.3%, respectively.…”
Section: Occurrence Of Pathogenic Microorganisms and Foodborne Outbrecontrasting
confidence: 55%
“…The undercooked meat and meat products, particularly poultry products have been known as a major source of Salmonella serotypes; however, other food products such as fresh produce, dairy products, and low a w foods have been found to be contaminated with different Salmonella spp. (Beuchat et al, 2013;Chávez-Martínez et al, 2019;Cruz et al, 2019;Cunha-Neto et al, 2019;Mendonça et al, 2019). Salmonella can be eliminated from foods by pasteurization of high a w foods such as liquid milk or juices (Beuchat et al, 2013) or using the microwave processing of low a w foods such as infant milk (Portela et al, 2019), which indicates the susceptibility of Salmonella to heat.…”
Section: Introductionmentioning
confidence: 99%
“…The surface of fruits, water, equipment and utensils, the adopted packaging, and the handlers themselves can be contamination sources (Olaimat and Holley 2012;Kamala and Kumar, 2018). Also, it is necessary to highlight that contamination with Salmonella can occur by animal manure as a fertilizer, water utilized for irrigation and animals that cross vegetable fields (Cruz et al 2019). In this context, it is essential the attention to the Good Agricultural Practices and Good Manufacturing Practices.…”
Section: Rte Fruitsmentioning
confidence: 99%
“…Schuh et al (2020) emphasize that the quality and shelf-life of minimally processed vegetables precisely depend on the production chain, since acquiring the raw material, to processing and commercialization. According to Cruz et al (2019), minimally processed vegetables are vulnerable to spoilage and then should be storage in 1-5°C. In this context, both those who process this type of food and the supermarkets that trade them need to guarantee the storage in refrigerated conditions.…”
Section: Rte Vegetablesmentioning
confidence: 99%
See 1 more Smart Citation